Because memory is also a prison. The Holocaust and the question of representing trauma in the memoirs of Ruth Elias and Ruth Klüger - Simões, Anabela Valente (2012)
Holocaust representations performed by male survivors such as Primo Levi or Elie Wiesel became the “norm” in the aftermath of WWII. Nonetheless, and despite the unquestionable canonical value, their narratives are not unique icons of the marking and traumatic experiences of that particular past. In actual fact, this historical moment became representation object for many female authors who, after overcoming a long latency period in which it was not yet possible to face trauma and work it through, finally found the strength to break the silence and tried to come to terms with the past through the process of writing. In this essay I intend to examine two distinctive autobiographical accounts written by women. On the one hand, Ruth Elias - who as a young Jewish from Czechoslovakia was taken to Auschwitz while several months pregnant - depicts with painful detail the experience of survival in the Nazi camps in her internationally acclaimed memoir Die Hoffnung erhielt mich am Leben. On the other hand, Austrian Jewish survivor Ruth Klüger accomplishes the following tasks in her praised novel weiter leben: the narration of her traumatic, haunted memories of the past and, simultaneously, an acute reflection upon past and contemporary complex issues. Herein Klüger assumes a provocative, sarcastic and defying attitude by examining sensitive matters such as disrupted parental relationships during the Jewish persecution, current complex relationships between Jews and Germans and even some Jewish patriarchal conventions which, according to the author’s perspective, seem to deny women their right to hold traumatic memories.